Partial Equilibrium Thinking, Extrapolation, and Bubbles - Bastianello, Francesca; Fontanier, Paul (Review of Financial Studies, 2026)
Abstract We develop a dynamic theory of “Partial Equilibrium Thinking” (PET), which micro-founds time-varying return extrapolation: extrapolative beliefs are present at all times, but only sometimes manifest themselves in explosive ways. We formalize the distinction between normal times shocks and “displacement shocks,” and study their interaction with extrapolative beliefs. In normal times, PET generates constant extrapolation and momentum. After a displacement shock that increases uncertainty, PET leads to stronger and time-varying extrapolation, triggering bubbles and endogenous crashes. Our theory sheds light on both market dynamics in normal times and Kindleberger’s narrative of bubbles within a unified framework.